MAPK blockade, toxicities, pathogenesis and management - Moreira, Alvaro; Lebbe, Celeste; Heinzerling, Lucie (Current Opinion in Oncology, 2021)
Purpose of review BRAF/MEK inhibitor has changed the treatment landscape in patients with advanced and metastatic melanoma with prolonged overall survival and progression-free survival. Since three treatment combinations exist with similar efficacy therapy decisions are often made based on the side effect profile. Additionally, on-target side effects or class effects have to be properly managed to ensure treatment adherence. Recent findings Sequential treatment with BRAF/MEK inhibition and immunotherapy might increase toxicity with a sepsis-like syndrome and triple therapy with concomitant BRAF/MEK inhibition and anti-PD1/PD-L1 antibody therapy induces severe side effects in the vast majority of patients. Toxicity of combination therapy with BRAF/MEK inhibitors is generally manageable, reversible and infrequently associated with treatment discontinuation. In case of persisting off-target effects the change to another combination therapy can resolve side effects.
CRIS-Team WoS Importer:2021-02-26